(untitled) (Jurnal Bahasa, 2010)
This article focuses on the language use in counselling sessions conducted by trainee counsellors at Universiti Malaysia Sarawak (UNIMAS). Research was conducted to identify the common speech acts used by trainee counsellors during counselling sessions in order to influence their clients (students). The research also aims to test the validity of the societal perception of counselling services as "advisory services". The research applies linguistic methodology and the speech act theory, in particular speech act categorisation (Bach & Harnish, 1979) to language behaviour in counselling practices. This form of categorization, with its four major speech act categories - constatives, directives, commisives and acknowledgement was chosen based on its precision and its ability to describe the linguistic differences found in speech acts. A total of 30 UNIMAS counselling programme students (trainee counsellors) of UNIMAS were sellected for this research. Their counselling session were recorded and transcribed in order to identify which was the most dominant speech act. It was found that the most dominant category is "question". This accorded with the main objective of the counseling sessions, which was to identify the clients’ problems. This proves that the societal view of counselling services as being predominantly advisory in nature is wrong. The findings of this research can be used as reference and guide by readers and language researchers, particularly those who are involved in the counselling field. Keywords: language use, speech act, counselling, trainee counsellors